2021
DOI: 10.1108/jec-08-2021-0117
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the interconnection between governance mechanisms and firm performance: evidence from Vietnamese listed firms

Abstract: Purpose Corporate governance plays a critical role in solving agency problems. However, previous findings on how governance mechanisms lead to high firm performance are inconclusive. Additionally, this relationship has not been well addressed in the context of transitional countries where governance systems and mechanisms are weak, leaving a gap for research. Hence, this study aims to shed light on the effects of four key governance components, namely, ownership concentration, chief executive officer duality, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 88 publications
0
1
0
1
Order By: Relevance
“…The presence of women in companies also has a detrimental influence on FP because women are seen as less capable of making difficult decisions (Mínguez-Vera & Martin, 2011). However, the current results do not support those reported by previous studies (Dissanayake et al, 2021;Molinero-Díez et al, 2022;Tran et al, 2022), thus showing that WBoC positively affects FP.…”
Section: Women Board Of Commissioners and Firm Performancecontrasting
confidence: 99%
See 2 more Smart Citations
“…The presence of women in companies also has a detrimental influence on FP because women are seen as less capable of making difficult decisions (Mínguez-Vera & Martin, 2011). However, the current results do not support those reported by previous studies (Dissanayake et al, 2021;Molinero-Díez et al, 2022;Tran et al, 2022), thus showing that WBoC positively affects FP.…”
Section: Women Board Of Commissioners and Firm Performancecontrasting
confidence: 99%
“…For example, in Pakistan, WBoC at state-owned enterprises (SOE) was found to have a positive effect on FP (Ullah, Fang & Jebran, 2020). Meanwhile, Tran et al (2022) found that increased gender diversity on boards of companies going public in Vietnam increased FP. There was also a strong relationship between the percentage of female board of commissioners and firm performance (Tleubayev et al, 2020).…”
Section: Women Board Of Commissioners (Wboc) and Firm Performance (Fp)mentioning
confidence: 99%
See 1 more Smart Citation
“…Quando são utilizados os mecanismos apropriados de governança corporativa, o desempenho das organizações pode ser melhorado (Tran et al, 2022). Isso se mostra ainda mais importante quando as empresas estão localizadas em países com fraca proteção legal, uma vez que as práticas de governança corporativa tendem a proteger os investidores de possíveis perdas (Chen et al, 2009).…”
Section: Introductionunclassified
“…By contrast, as a case-based approach, fsQCA emphasizes combinatorial effects (Woodside, 2013). Moreover, drawing on the set theory and complexity theory, fsQCA enables examinations of the asymmetric relationships between conditions and their outcomes (Huarng, 2016; Tran et al , 2022). Afonso et al (2018) explained these asymmetric relations in two terms: equifinality and multifinality.…”
Section: Introductionmentioning
confidence: 99%